Targeting interferon-stimulated gene of 20 kDa protein (Isg20) inhibits ribosome biogenesis to ameliorate the progression of renal fibrosis. - Xiaoming Liu; Huijuan Wang; Kai Wang; Ying Liu (PLoS ONE)
Chronic kidney disease (CKD) is a global health issue that significantly threatens human health, with its incidence increasing annually. Renal fibrosis is characterized by the progressive loss of kidney function, leading to significant morbidity and mortality. Although ribosome biogenesis has been reported to be increased in several kidney diseases, its role in renal fibrosis remains unclear. This study investigates the role of the interferon-stimulated gene of 20 kDa protein (Isg20), an RNA exonuclease involved in several stages of ribosome biogenesis, in the progression of renal fibrosis. Bioinformatics analysis of Gene Expression Omnibus (GEO) datasets identified upregulation of ribosome biogenesis-related genes and Isg20 expression in renal fibrosis samples. Using the unilateral ureteral obstruction (UUO)-induced renal fibrosis mouse model, we confirmed elevated Isg20 expression, promoted renal fibrosis, and increased ribosome biogenesis. Knockdown of Isg20 significantly reduced ribosome biogenesis, ameliorated kidney damage, inhibited pro-inflammatory cytokines levels and renal fibrotic changes, and decreased endoplasmic reticulum stress and cell apoptosis. Our findings suggest that Isg20 exacerbates renal fibrosis by promoting ribosome biogenesis, ER stress and cell apoptosis highlighting a potential therapeutic target for renal fibrosis treatment.